PERAN MPK PAI DALAM MEMBANGUN KARAKTER MAHASISWA STIESIA SURABAYA - Dewi Mutmainnah (Piwulang: Jurnal Pendidikan Agama Islam, 2019)
This study aims to determine and understand the role of the Personality Development Course (MPK) of Islamic Religious Education (PAI) and its effectiveness in building the character of STIESIA Surabaya students. This research is a qualitative research using data analysis of Spradley model and taking the location of research in the STIESIA Surabaya campus. The result of this study found that character building through the courses of Islamic Religion in STIESIA was pursued with 3 strategies, namely : (1) Moral Knowing, was the first stage carried out by Islamic Religious Education lecturers and oriented to mastering knowledge of moral values noble; (2) Moral Loving, the stage where after students are able to master knowledge of noble moral values, the lecturers touches the emotional aspects of the soul and heart of students so that they love these nobel moral values and â€œneedâ€ to do it in their daily lives;Â  and then (3) Moral Doing, is the peak stage which is said to be a sign of successÂ  in building the character of students that is practicing noble character in real life everyday. Form the observations and interviews, the courses on Islamic Religious Education at STIESIA managed to build the character of students for the better.Penelitian ini bertujuan untuk mengetahui dan memahami peran Mata Kuliah Pengembangan Kepribadian (MPK) Pendidikan Agama Islam (PAI) serta efektivitasnya dalam membangun karakter mahasiswa STIESIA Surabaya. Penelitian ini adalah penelitian kualitatif dengan menggunakan analisis data model Spradley dan mengambil lokasi penelitian di lingkungan kampus STIESIA Surabaya. Hasil penelitian ini menemukan bahwa Pembangunan karakter melalui mata kuliah Pendidikan Agama Islam di STIESIA ditempuh dengan 3 strategi yaitu : (1) Moral Knowing/ Learning to Know, merupakan tahap pertama yang dilakukan yang berorientasi kepada penguasaan pengetahuan tentang nilai nilai akhlak mulia; (2) Moral Loving, tahapan dimana dosen menyentuh aspek emosional jiwa dan hati mahasiswa agar mencintai nilai-nilai akhlak mulia tersebut dan â€œbutuhâ€ untuk melakukannya dalam kehidupan sehari-hari; dan (3) Moral Doing, adalah tahapan puncak dalam membangun karakter mahasiswa yaitu mempraktikkan akhlak mulia dalam kehidupan sehari-hari. Berdasarkan pengamatan dan wawancara Mata kuliah Pendidikan agama Islam di STIESIA berhasil membangun karakter mahasiswa menjadi lebih baik.